The use of hair as a manifestation of cultural and gender identity in the works of Tracey Rose - Meyerov, Lee-At (My University, 2008)
ABSTRACT This research report investigates the manifestation of hair as a symbol of cultural and gender identity as is seen in selected works of South African artist Tracey Rose, whose usage of her own culturally specific hair and body serves as metaphor through which she critically engages with issues surrounding the gendered and racialized body. The report will explore the ways in which Rose both in her video piece Ongetiteld (1996) and her performance video installation Span II (1997) challenges and subsequently deconstructs the rigidly defined monoliths of ‘Woman’, ‘femininity’, and the racially constructed category of ‘Coloured’, assigned and imposed on her during the Apartheid era. Rose’s work, highlighting the extent to which the conceptualization of gender and racial identity are bound and read off the body’s corporeality, relates to my own artistic practice, whereby I examine the metaphorical functioning of skin, as a corporeal ‘text’ and parchment, facilitating the inscription of my own cultural, religious and linguistic Otherness.
Keywords: cultural and gender identity; hair; race; feminism; South African artist Tracey Rose